Influence of dietary factors on colorectal cancer survival. Issue 6 (1st June 2003) - Dray, X; Boutron-Ruault, M-C; Bertrais, S; Sapinho, D; Benhamiche-Bouvier, A-M; Faivre, J
Abstract : Background: Diet has been identified as a major determinant of colorectal cancer (CRC) but little is known of its influence on CRC survival. Aims: To study the influence of dietary factors on survival in patients who had undergone potentially curative CRC surgery. Patients: Among 171 patients included in a case control study of CRC aetiological factors, 10 year survival data on 148 patients who underwent resection of the tumour for potential cure were obtained from a Registry of Digestive Tumours. Methods: Tertiles of food and nutrient intakes were entered into Cox proportional hazards survival models, controlling for age, sex, tumour stage, and tumour location. Results: Only five year survival was influenced by the pre-diagnosis diet. High energy intake, as a result of high carbohydrate, protein, and lipid intake, was strongly related to increased survival. Five year relative risk of death for the highest versus the two lowest tertiles of energy intake was 0.18 (95% confidence interval 0.07; 0.44). This effect was similar in both sexes, for the colon and for the rectum. It was stronger in patients with N+/M+ tumours (relative risk 0.06) than in those with less advanced tumours (relative risk 0.37; stage-energy interaction term non-significant). No specific food or nutrient could be identified as having prognostic significance. Conclusions: Whether high energy intake selects less severe tumoral clones or modifies antitumoral immunity remains unclear. Larger series need to be investigated before conducting intervention studies but our findings should prompt nutritional follow up in CRC patients.